(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Vishwachi is one among the Vataja Nanatmaja Vyadhi. It affects the neck and upper extremities with signs and symptoms like Ruk, Stambha, Toda, Karmakshaya and Chestapaharana of Bahu as explained by different Acharyas. Dalhana opines that the condition resembles Gridhrasi which affects the lower limb, and is of two types, Vataja and Vatakaphaja. The clinical presentation of Vishwachi is similar to that of Cervical Spondylosis which is a degenerative condition of the cervical spine. Being an Urdhwajatrugatavikara, Nasya karma has been mentioned as the prime line of treatment. Dhatukshaya can be considered as main factor leading to a condition like Vishwachi. Hence in order to find an effective solution in this condition, Snehana Nasya with Shuddhabala Taila has been taken for the study. Objective: To evaluate the effect of Snehana Nasya in Vishwachi. Methods: It is an open label single arm clinical trial with pre-test and post-test design. A special proforma was prepared considering history taking, physical examination and assessment needed for the condition. The study was carried out in 30 patients of Vishwachi. Nasya karma was done by instilling 16 Bindu of Shuddhabala Taila for 7 days. Data was collected on the 1st day before treatment and 7th day after treatment. Results: The reduction in severity of symptoms was statistically analysed by Wilcoxon sign rank test. Significant improvement was found in all the patients. Conclusion: Analysis of overall effect of the treatment showed significant results. Hence Nasya karma with Shuddhabala Taila was found to be effective in Vishwachi.